Current Trends in the Radiodiagnosis of Hodgkin’s Lymphoma in Children - K. A. Khasanova; I. E. Tyurin (Вестник рентгенологии и радиологии, 2019)
The main techniques used for the primary staging and evaluation of treatment response in children with Hodgkin's Lymphoma (HL) are contrast-enhanced computed tomography (CECT) and 18F-fl.uorodeoxygLucose positron emission tomography combined with computed tomography (18F-FDG PET/CT). Both techniques have a high sensitivity and specificity. Despite this, a single diagnostic protocol has not yet been developed for children with Hodgkin's Lymphoma. The simultaneous use of the two methods is not aLways appropriate at each treatment stage. The unreasonabLe consecutive performance of CECT and 18F-FDG PET/CT in children with HL increases the cumulative radiation dose for a child and the consumption of equipment resources. This article describes in detail the main advantages and disadvantages of CECT and 18F-FDG PET/CT at all stages of management of children with HL, as well as various approaches for current diagnostic algorithms in the primary staging of HL in children and in the evaluation of treatment efficiency.Literature was sought using the following databases: Pubmed, Uptodate, ClinikalKey, CyberLen-inka, and Russian Science Citation Index (RSCI).